2020
DOI: 10.1021/acsenergylett.0c01384
|View full text |Cite
|
Sign up to set email alerts
|

Ionothermal Route to Phase-Pure RuB2 Catalysts for Efficient Oxygen Evolution and Water Splitting in Acidic Media

Abstract: Developing high-efficiency and stable oxygen evolution reaction (OER) materials remains a great challenge, especially in an acidic medium. In this study, we report the first synthesis of phase-pure RuB2 by using a salt melt of potassium chloride and lithium chloride as the solvent. When used as an electrocatalyst in 0.5 M sulfuric acid, the as-prepared RuB2 needs an overpotential of only 223 mV for the OER to produce an operationally relevant current density of 10 mA cm–2. This is almost the smallest overpoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 50 publications
(74 reference statements)
3
106
0
Order By: Relevance
“…From the deconvoluted spectrum of Ru 3p state, the couple peaks at 462.1 and 484.3 eV are associated with Ru 3p 3/2 and Ru 3p 1/2 , respectively (Figure 2 c). [3, 18] Figure 2 d shows that the separate subpeaks at 163.0 and 164.2 eV are consistent with S 2p 3/2 and S 2p 1/2 states, respectively [19] . To compare the chemical states of heterostructure material with phase‐pure materials, further XPS analyses were conducted.…”
Section: Figurementioning
confidence: 80%
See 1 more Smart Citation
“…From the deconvoluted spectrum of Ru 3p state, the couple peaks at 462.1 and 484.3 eV are associated with Ru 3p 3/2 and Ru 3p 1/2 , respectively (Figure 2 c). [3, 18] Figure 2 d shows that the separate subpeaks at 163.0 and 164.2 eV are consistent with S 2p 3/2 and S 2p 1/2 states, respectively [19] . To compare the chemical states of heterostructure material with phase‐pure materials, further XPS analyses were conducted.…”
Section: Figurementioning
confidence: 80%
“…As for the hydrogen production, the acidic water splitting devices employing mature proton exchange membrane (PEM) technology afford excellent hardware environment for large‐scale commercial applications [1a, 2] . The use of PEM and favorable reaction mechanism bring multiple strengths, such as cost advantage, high proton conduction, fewer side effects and convenient gas separation [2b, 3] . However, both electrodes of PEM‐water splitting (PEMWS) devices require certain electrocatalysts to effectively facilitate the sluggish kinetic processes [1a, 4] .…”
Section: Figurementioning
confidence: 99%
“…But the oxidation behavior at high voltage would cause devitalization, and the effusion of lattice oxygen would result in the dissolution of active species, rendering them unstable during OER process [10] . Thus, designing oxygen‐free Ru‐based catalysts with suitable morphology and electron structure might alleviate the deactivation behavior, meanwhile promote their intrinsic activity and durability [3, 11] …”
Section: Figurementioning
confidence: 99%
“…The results showed that RuB 2 needed less energy for the rate-determining step (formation of *OOH), so the OER activity was improved (Figure 3d, e). [31] In addition, the OER activity of RuTe 2 was also [8] and c) RuP 2 @PNC [20a] used in DFT calculations and calculated free energy diagrams of the catalyst samples for HER. [17b] Reproduced with permission.…”
Section: Gibbs Free Energy Of Key Intermediatesmentioning
confidence: 99%
“…d), e) Free energetic pathways of RuB 2 and RuO 2 for acidic OER at U = 0 V. Reproduced with permission. [31] Copyright: 2020, American Chemical Society. f) CO 2 RR and g) nitrite reduction on pure Pd (111) and TeÀ Pd (111) surfaces.…”
Section: Gibbs Free Energy Of Key Intermediatesmentioning
confidence: 99%